Development of a Water Bill Arrears Information System Based on Microsoft Access and Visual Basic 6.0 for PDAM Tirta Mon Krueng Baro - Aulia, M. Yasir (Journal Dekstop Application (JDA), 2024)
This study addresses the development of an automated water bill arrears management system for PDAM Tirta Mon Krueng Baro, aiming to replace the previous manual method that relied on Microsoft Excel. The old system resulted in errors, delays in report generation, and difficulties in tracking overdue payments, which impacted both financial management and customer service. The newly designed system utilizes Microsoft Access and Visual Basic 6.0 to streamline data entry, reduce errors, and enable efficient tracking of overdue bills. With a structured database and normalized tables, the system improves data accuracy, eliminates redundancy, and speeds up reporting processes. The adoption of this system ensures real-time updates and quicker decision-making, which enhances financial management. The user-friendly interface and automated features facilitate smooth implementation and greater user acceptance. By transitioning to a computerized system, PDAM Tirta Mon Krueng Baro can enhance operational efficiency, minimize errors, and improve customer satisfaction. The study demonstrates the positive impact of adopting modern technology to optimize service delivery in public utilities, offering a more effective approach to managing billing processes and overdue payments.